RESPON PERTUMBUHAN ELEUSINA INDICA PADA TANAH TERKONTAMINASI MINYAK BUMI UNTUK RANCANGAN HANDOUT PADA MATERI PERTUMBUHAN DAN PERKEMBANGAN KELAS XII SMA - Fransiska Flonia; Suwondo Suwondo; Irda Sayuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was conducted to find growth response Eleusina indica on petroleum contaminated soil which used for handout design in growth and development materials in senior high school grade XII, which was conducted in September 2018 until February 2019. This research used an experimental method with Completely Randomized Design (CRD). Parameters used include vegetative growth of plants crops shoots number, stem height, leaf length and biomass of plant then degradation rate (%) TPH. The data of growth response Eleusina indica on petroleum contaminated soil with total petroleum hydrocarbon (TPH) concentration which differences were an analysis of variance (ANOVA) continued Duncan's test if there are significant differences. While for handout design is done with two stages, namely analyze stage and design stage. The result showed that the Eleusina indica plant was able to grow on petroleum contaminated soil which can be seen of vegetative growth response. Besides, the Eleusina indica plant has the ability to degrade TPH with a percentage of 0,202-0,821%. It was concluded that Eleusina indica plant was able to well adapt to petroleum contaminated soil. The result of this research was further developed into handout in growth and development materials in senior high school grade XII.Key Words : Growth, Eleusina indica, Fitoremediation, Petroleum contaminated soil, Handout.